DELONIX REGIA BOJ. EX. HOOK RAFFIN; FAMILY: FABACEAE, BARK METHANOL EXTRACT PHYTOCHEMICAL PROFILE AND POTENTIAL THERAPEUTIC EVALUATION - SHIVAMALLU, ARPITHA; SEKHAR, SHAILASREE (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: The aim of this study was to evaluate the antioxidant, anti-inflammatory, and anti-cancer potencies of the Delonix regia bark, a first of its kind. Methods: The bark was extracted sequentially in Soxhlet apparatus with hexane, chloroform, and methanol in the increasing order of polarity. These extracts were subjected to find its antioxidant activity and total phenol content. Antibacterial activity against human pathogenic bacteria was tested. The anti-inflammatory properties were elucidated by its capacity to inhibit 15-lipoxygenase (LOX) and human cyclooxygenase (COX)-2. Cell cytotoxic capacity was evaluated against MCF-7 cells breast cancer cell lines. Results: Liquid chromatography (LC)-Mass Spectroscopy (MS) fingerprint of the methanol extract identified a total of 14 polyphenols, of which five were structurally characterized based on their mass-charge ratio [M-H]− peak, UV-vis absorption in comparison to published data. Antibacterial activity by disk diffusion inhibited human pathogenic bacteria. Bacterial biofilm inhibition capacity of extract (750 mg) imaged by confocal laser scanning microscopy revealed loss of microcolonies. Extract when tested for 15-LOX inhibition exhibited IC50 values of 94.5 ± 1.23 mg.mL−1 by enzyme kinetics studies using spectrophotometric techniques. Similarly, it could inhibit COX-2 enzyme at relatively lower concentrations (32.18 ± 1.91 mg.mL−1). Further, it quenched free radicals produced by Fentons’ reagent studied by DNS-nicking assay indicating its strong antioxidant property with the capacity to protect DNA. In vitro cytotoxicity was evaluated by 3-(4,5-dimethylthylthiazol-2-yl)-2,5-diphynyl tetrazolium bromide assay and apoptosis induced in MCF-7 cells was assessed morphologically. Conclusion: Our data suggest that D. regia bark methanol extract exerts its therapeutic activity for further pharmaceutical evaluations. Further studies are necessary to determine the mechanisms of these pharmacological properties.